2019
DOI: 10.1200/jgo.18.00248
|View full text |Cite
|
Sign up to set email alerts
|

Life Without a Breast: Exploring the Experiences of Young Nigerian Women After Mastectomy for Breast Cancer

Abstract: PURPOSE The majority of women managed for breast cancer in Nigeria are relatively young, many in their forties. Mastectomy, the most common surgical treatment, raises psychosocial concerns. Understanding these concerns may help address the fears of women who refuse treatment and aid in the care of those who have had mastectomy. METHODS Using qualitative methods, we purposively sampled women 45 years of age and younger who underwent mastectomy for breast cancer at a Nigerian teaching hospital. One-on-one in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 21 publications
5
49
0
Order By: Relevance
“…Furthermore, difficulties in sexual life consisting of posttreatment disturbances in body image and feelings of unattractiveness seem to be highly prevalent among BC survivors [34]. Consistent with our results, a qualitative study on Nigerian women after mastectomy demonstrated that mastectomy had a remarkable influence on the women's perceptions of femininity and reduced their sexual function [35]. A phenomenological study in Jordan showed that many women with BC were dissatisfied with their appearance and particularly were sensitive regarding their sexual unattractiveness due to cancer treatments.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, difficulties in sexual life consisting of posttreatment disturbances in body image and feelings of unattractiveness seem to be highly prevalent among BC survivors [34]. Consistent with our results, a qualitative study on Nigerian women after mastectomy demonstrated that mastectomy had a remarkable influence on the women's perceptions of femininity and reduced their sexual function [35]. A phenomenological study in Jordan showed that many women with BC were dissatisfied with their appearance and particularly were sensitive regarding their sexual unattractiveness due to cancer treatments.…”
Section: Discussionsupporting
confidence: 87%
“…Phenotypically, evidence suggests a relatively young median age of diagnosis and higher proportion of triple‐negative breast cancer (TNBC) 7 . These biological variables are confounded by delays in presentation that result in a significant burden of advanced stage disease 8‐10 . Understanding these factors and how they relate to poor outcomes are central to the design and implementation of effective interventional programs.…”
Section: Introductionmentioning
confidence: 99%
“…Combined brief psychosexual intervention and counseling after a mastectomy is necessary to help post-mastectomy females in body image self-acceptance and perceived partner acceptance positively [ 49 ]. Excellent social support [ 50 ] and strong married relationships can improve the quality of sexual life after mastectomy [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding implies that unique post-operative care for each gender identity is demanded. As men are a minor group of breast cancer patients and gender-classified data collections for LGBTQ are scarce, studies regarding their cases were not able to establish a direct relationship between mastectomy and sexuality [ 9 ]. Therefore, this short narrative is a call for diverse gender classification in data collection systems and more research into sexuality among LGBTQ and men breast cancer patients after mastectomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation